Penyuluhan Tentang Suntik Tetanus Toksoid Kepada Ibu Hamil Primigravida Di Pesisir Loun - Netty Taribuka; Mirna Heluth (Poltekkes Kemenkes Denpasar, 2019)
In 2008 there were cases of Tetanus Neonatorum with 91 cases of death or a Case Fatality Rate (CFR) of 55%. Most of the cases of Tetanus Neonatorum were babies whose deliveries were assisted by traditional birth attendants. Tetanus neonatorum is a tetanus disease that occurs in neonates (infants less than 1 month old) caused by Clostridium tetani, which is a germ that releases toxins that attack central nervous system. Risk factors that cause neonatal tetanus are delivery that does not meet cleanliness, namely umbilical cord care does not meet health requirements and administration of Tetanus Toxoid immunization to pregnant women is not carried out or is incomplete or not in accordance with program provisions. TT immunization is one solution to prevent tetanus neonatorum (TN). WUS who are the targets of TT immunization are women aged 15-49 years consisting of pregnant women (pregnant women) and non-pregnant women. TT immunization on WUS is given as many as 5 doses at certain intervals, starting before and or during pregnancy which is useful for lifelong immunityKeywords: tetanus, pregnancy, primigravida.